Penerapan Pemeriksaan Saksi Secara Bersama-Sama Dalam Persidangan Perkara Pidana - Uun Ulfiana; Y.A Triana Ohoiwutun; Samuel Saut Martua Samosir (Pusat Riset dan Inovasi Nasional, 2023)
The examination of witnesses regulated by Act No. 8 of 1981 on the Code of Criminal Procedure Law (hereinafter referred to as KUHAP) is a provision concerning formal criminal law. In the case No. PDM-242/JKTSL/10/2022 with the accused Ferdy Sambo (FS) and the case N. P.D.M-246/Jktsl/10/2022 with Princess Chandrwati (PC) there is an event conducted examination of witnesses jointly, becoming a material of investigation, whether such examination can be carried out simultaneously considering the witness in giving explanations must be independent. To respond to the focus of research in this research use normative jurisprudential research methods with conceptual approaches and legislative approaches. The conclusion is that the joint examination of witnesses is based on Article 172 (1) of the Convention. Accordingly, the public prosecutor or the accused or the legal counselor may prepare a witness of a qualitative nature, subject to the provisions of applicable law, so that the testimony of the witnesses may have a valid proof force. Furthermore, it is expected that the law enforcement agencies will be able to carry out witness examination procedures accurately and honestly in order to the objective of the examination in the trial, which is to material truth.